Translational inhibitory conditions and mechanistic target of rapamycin (mTOR) protein expression – an internal ribosome entry site (IRES) solves the problem - Marques-Ramos, Ana (2015)
Regulation of mRNA translation plays a major role in controlling gene expression, since it allows rapid cellular responses to external stimuli. Translational control can be transcript-specific via cis-acting elements, such as internal ribosome entry sites (IRESs). mRNA translation initiation driven by IRES elements is independent of some canonical initiation factors that are inhibited by cellular stresses or in some physiological/pathophysiologic settings. Accordingly, IRES-dependent translation allows continued protein synthesis in conditions of global canonical mRNA translation inhibition. The mechanistic target of rapamycin (mTOR) is a conserved serine/threonine kinase that senses cellular nutrient- and energy- status, acting namely on the protein synthesis machinery. Major advances are emerging regarding the effects and regulators of mTOR signaling pathway, however, regulation of mTOR gene expression, specifically at the translational level, is not well known. Here, it is shown that the 5’ untranslated region (5’UTR) of the human mTOR mRNA contains an IRES element that allows cap-independent translation of mTOR. In addition, it is demonstrated that IRES-dependent translation of mTOR is stimulated by hypoxia with associated eIF2α phosphorylation. The anti- and pro-apoptotic outcomes of the response to endoplasmic reticulum (ER) stress also stimulate mTOR IRES activity, with a more pronounced effect in the pro-apoptotic phase with associated eIF2α phosphorylation. Furthermore, it is illustrated that mTOR IRES activity is potentiated by mTORC1 inactivation, suggesting a feedback loop in order to maintain mTOR expression. These data point out a novel regulatory mechanism of mTOR gene expression that integrates the protein profile rearrangement triggered by global translational inhibitory conditions.